A new PAX6 mutation in familial aniridia. Issue 6 (June 1995) - Hanson, I; Brown, A; van Heyningen, V
Abstract : Aniridia (lack of iris) is caused by loss of function mutations in one copy of the PAX6 gene. Here we present a new PAX6 splice mutation in a family with autosomal dominant aniridia. The mutation is a single nucleotide change which, although occurring within an exon, affects the splice junction consensus and results in skipping of that exon.